Materials, productions, exchange network and their impact on the societies of Neolithic Europe ; proceedings of the XVII UISPP World Congress (1-7 September 2014, Burgos, Spain). - Guilaine, Jean (Archaeopress archaeology., 2017)
This edited volume examines the impact on societies in Neolithic Europe of materials, productions and exchange networks.